Blending Optimization of Coals with Different Chemical and Thermal Properties with Linear Programming - Turan, Sema Nur; Adigüzel, Deniz (Fırat University, 2024)
Thermal power plants are facilities that have an important place in electricity production. However, production costs, sustainable use of resources, and ensuring product quality are major problems for thermal power plants. Energy consumption optimizations are needed to solve this problem. In this study, coal produced from four different regions (Orhaneli Basin, Keles Basin, Seyitömer Basin, and Tunçbilek Basin) was used as a constraint with the linear programming model where the cost was minimized and the limit values suitable for use in the thermal power plant were used, in double, triple and quadruple coal. were blended and mixture models were created. Accordingly, a total of 6 blend groups were created and the established models were solved with the Lingo program. According to this; 37.2% from Orhaneli quarry in the 1st group - 62.8% from the Keles quarry, 15.6% from the Orhaneli quarry in the 2nd group - 84.4% from the Seyitömer quarry, 88.9% from the Keles quarry in the 3rd group - 11.1% from the Tunçbilek quarry, in the 4th group, 75% from Tunçbilek quarry - 25% from Seyitömer quarry, in the 5th group, 43% from Orhaneli quarry - 52% from Keles quarry and 5% from Tunçbilek quarry, and in the 6th group, 29% from Orhaneli quarry, 64% from Seyitömer quarry and 7% from Tunçbilek quarry. It was concluded that it should be used in proportion. Thus, coals with different chemical and thermal properties have been made available in thermal power plants in certain proportions through blending optimization. According to the calculations made, it is seen that among the total six blend groups, Orhaneli / Keles / Tunçbilek 3-bleed blend and Orhaneli / Keles 2-bleed blends give the lowest values in terms of costs.

Termik santraller elektrik üretiminde önemli bir yere sahip olan tesislerdir. Fakat üretim maliyeti, kaynakların sürdürülebilir kullanımı ve ürün kalitesinin sağlanması termik santraller için büyük bir problemdir. Bu problemin çözülmesi için enerji tüketimi optimizasyonlarına ihtiyaç duyulmaktadır. Bu çalışmada, maliyetin minimize edildiği ve termik santralde kullanılması uygun sınır değerlerin kısıtı olarak kullanıldığı doğrusal programlama modeli ile dört farklı bölgeden üretilen (Orhaneli havzası, Keles Havzası, Seyitömer Havzası ve Tunçbilek Havzası) kömür, 2’li, 3’lü ve 4’lü olarak harmanlanmış ve karışım modelleri oluşturulmuştur. Buna göre toplam 6 harman grubu oluşturulmuş ve kurulan modeller Lingo programıyla çözülmüştür. Buna göre; 1. grupta Orhaneli ocağından %37,2 - Keles ocağından %62,8, 2. grupta Orhaneli ocağından %15,6 - Seyitömer ocağından %84,4, 3. grupta Keles ocağından %88,9 - Tunçbilek ocağından %11,1, 4.grupta Tunçbilek ocağından %75 - Seyitömer ocağından %25, 5. grupta Orhaneli ocağından %43 – Keles ocağından %52 ve Tunçbilek ocağından %5 ve 6. grupta ise Orhaneli ocağından %29, Seyitömer ocağından %64 ve Tunçbilek ocağından %7 oranında kullanılması gerektiği sonucuna varılmıştır. Böylece farklı kimyasal ve ısıl özelliklere sahip kömürler harmanlama optimizasyonu ile belirli oranlarda termik santrallerde kullanılabilir duruma getirilmiştir. Yapılan hesaplamalara göre; toplam 6 harman grubu içerisinde maliyetler açısından Orhaneli / Keles / Tunçbilek 3’lü harmanı ve Orhaneli / Keles 2’li harmanlarının en düşük değerleri verdiği görülmektedir.
Farklı Kimyasal ve Isıl Özelliklere Sahip Kömürlerin Doğrusal Programlama ile Harmanlama Optimizasyonu
Keywords: Mine Design; Management and Economy; Maden Tasarımı; İşletme ve Ekonomisi; Mining Methods and Mine System Analysis; Madencilik Yöntemleri ve Maden Sistem Analizi